SEED DORMANCY AND GERMINATION IN Hymenachne amplexicaulis (Caderno de Pesquisa, 2016)
Hymenachne amplexicaulis (Rudge) Nees is a grass of fast growth and high production of seeds, native to Central and South America, may cause ecological damage, which is introduced. This study aimed to identify the mechanisms of seed dormancy of H. amplexicaulis. Was evaluated the efficiency of gibberellic acid (0.05%) and potassium nitrate (0.2%) in two lots of seeds stored for 6 and 18 months. The periods of hydration of 0 (control), 3, 6, 9, 12, 24, 36 and 48 hours at a temperature of 23± 1°C and removal of the glumes, were evaluated in the lot with six months of storage. Seed germination was higher when exposed to potassium nitrate, while gibberellic acid did not promote germination. Seed hydration and removal of the glumes caused an increase in percentage and germination speed index.